Dynamic accessibility of geosites: Evidence from long-term observations in the Belaya River valley (western Greater Caucasus) - Anna V. Mikhailenko; Dmitry A. Ruban (International Journal of Geoheritage and Parks)
Accessibility is an important property of geosites that is essential to their conservation and exploitation. Although many previous researchers took it into account, its full complexity is yet to be realized. Three large geosites in the valley of the Belaya River in the western Greater Caucasus were visited regularly for about a quarter of a century. In this study, the outer and inner accessibility of each considered geosite was assessed semi-quantitatively for five time slices of the 2001–2024 time span. The outer accessibility was examined for each entrance to the geosites, and the inner accessibility was examined for each principal functional zone of the geosites. The results revealed differences of the outer accessibility between the entrances of the same geosites and the inner accessibility between the functional zones of the same geosites. Moreover, it was found that the outer and inner accessibility could increase and decrease through time, and the above-mentioned spatial differences within geosites could also change. A proximity to settlements and tourism growth were among the main factors of the reported spatiotemporal dynamics. The outcomes of this study stressed the need for a much deeper understanding of such geosite properties as accessibility.